Pengaruh Koordinasi Camat Tehadap Keberhasilan Pembangunan di Kecamatan Singkil Kota Manado - Maryani, Ika; Rumapea, Patar; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The coordination in the implementation of development carried out by the Head in his capacity as head of the administrative area of the District, who was given the task to coordinate the activities of an operational nature. In conjunction with the coordination function, then Head efforts are undertaken on an ongoing basis can create a good working relationship with a subordinate even to institutions / agencies diwilayahnya partners, such as the urban / rural development that support the implementation. In accordance with the characteristics of the problems examined and the formulation of hypotheses that have been proposed previously, then the relevant quantitative approach to the application of the method used descriptive (Nazir 1988; Koentjaraningrat, 1997); and explanatory survey (Vredenbreght, 1981). Distribution of respondents as described in Table 3 it can be seen that of the 80 respondents were interviewed about the application function camat coordination in the implementation of the development, there were about 45 or Â± 56.3% of respondents stated that the application functions camat coordination in the implementation of development in the District Singkil is in the category "medium", 26 respondents or 32.5% were in the category of "high", and the remaining nine respondents, or about 11.3% are in the category of "low". That the application of the coordination function by Head and success of development (participation, standards of living and selfreliance) in the Regional District of Manado City Singkil can not be achieved optmal. Keywords: Coordination and development success.